The Relation Between Mathematics Philosophy And Culture-Based Learning Model - Hasibuan, Eka Khairani; Dewi, Izwita; Ahyaningsih, Faiz (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
The aim of this study is to study the correlation of mathematical philosophy with cultural-based learning models. The method of research used is the method of library research, i.e. conducting studies related to mathematical philosophy, philosophical mathematics learning, culture-based mathematic learning, the connection of mathematically philosopher with ethnomatematics, the relationship of mathematic philosophies with cultural-based learning models. The results of the research have been obtained that the philosofy of maths, the model of learning based on culture, and ethnomathematics have close connections in the context of understanding and teaching of Mathematics. Mathematical philosophy deals with the foundations of mathematical epistemology and ontology, while a culture-based learning model emphasizes the integration of values and cultural contexts in mathematics learning. Ethnomatematics refers to the study of mathematical ways of thinking in a particular culture. By understanding the cultures, traditions, and world views of a particular society, ethnomathematics can help develop more culturally relevant and meaningful learning models. Therefore, the interrelationship between mathematical philosophy, culture-based learning models, and ethnomathematics can create a more holistic and contextual approach to mathematics learning. Keywords: Mathematical Philosophy, Cultural Based Learning Model, Ethnomathematics